Development of Android apps for transmission line/circuit analysis - Soh, Xin Han (Nanyang Technological University, 2023)
The Android app for calculating transmission line is a tool designed to assist engineers and students in calculating various transmission line variables. The app utilizes a user-friendly interface and intuitive design to make complex calculations involved in transmission line analysis simple.